Genetic Diversity of Marrubium Species from Zagros Region (Iran), Using Inter Simple Sequence Repeat Molecular Marker - N. Salehi; N. Kharazian; B. Shiran (Journal of Sciences, Islamic Republic of Iran)
This study concerns the genetic diversity and taxonomic status of Marrubium species from central and south-west of Zagros region, Iran. It is investigated by Inter-Simple Sequence Repeat analysis. A total of 68 accessions from five Marrubium species were collected from their natural habitats. Molecular analysis was approved with 17 primers, of which 12 were carried out in the reaction mixture. Moreover, a data matrix was designed to estimate genetic parameters. To determine the genetic structure and taxonomic status, analysis of molecular variance, clustering analysis with UPGMA (Unweighted Pair Group Method Average) and the Jaccard similarity coefficient were estimated using NT-SYS-pc and Gene Alex software. Supplementary morphological evidences of calyx teeth features were also provided. The results of this study revealed that both sections Marrubium, Microdonta, and Ballota aucheri displayed a high percentage of polymorphism (PP=100%). In addition, their genetic diversity (Gst=0.99), number of effective alleles (Ne=1.53) and Shannon information index (I=0.51) showed a high percentage. Notably, all of the 12 primers produced reproducible bands. Analysis of molecular variance detected low quantities of gene variation among species (18%) from which high proportion of variation presented among populations within species (82%). Based on cluster analysis, M. cuneatum, M. vulgare and M. anisodon were definitely separated. Moreover, M. crassidens and M. vulgare were closely grouped. The calyx teeth features of M. cuneatum and M. crassidens revealed high variations which is consistent with molecular results. In conclusion, high genetic diversity in Marrubium species and accessions presents a valuable genetic resource in Zagros region, Iran.